2003
DOI: 10.1021/bi034939j
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Fully Functional Cysteine-Less Variant of Osmosensor and Proton-Osmoprotectant Symporter ProP from Escherichia coli and Its Application to Assess the Transporter's Membrane Orientation

Abstract: Transporter ProP of Escherichia coli is an osmosensor and an osmoprotectant transporter. Previous results suggest that medium osmolality determines the proportions of ProP in active and inactive conformations. A cysteine-less (Cys-less) variant was created and characterized as a basis for structural and functional analyses based on site-directed Cys substitution and chemical labeling of ProP. Parameters describing the osmosensory and osmoprotectant transport activities of Cys-less ProP-(His)(6) variants were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(102 citation statements)
references
References 37 publications
5
97
0
Order By: Relevance
“…Bacteria were cultivated as described previously for transport assays (12) in low-osmolality MOPS medium supplemented with arabinose (1 mM), and SDS-PAGE was performed as described by Laemmli (26) using Bio-Rad MiniProtean II cells (Bio-Rad Laboratories Ltd., Hercules, CA) (12% T, 2.67% C). The SDS loading buffer did not contain ␤-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were cultivated as described previously for transport assays (12) in low-osmolality MOPS medium supplemented with arabinose (1 mM), and SDS-PAGE was performed as described by Laemmli (26) using Bio-Rad MiniProtean II cells (Bio-Rad Laboratories Ltd., Hercules, CA) (12% T, 2.67% C). The SDS loading buffer did not contain ␤-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…For Western blotting, bacteria were cultivated as described previously for transport assays (12) in low-osmolality MOPS medium without arabinose. Cell extracts were separated by SDS-PAGE, and Western blotting was performed using anti-ProP antibodies as described previously (49).…”
Section: Methodsmentioning
confidence: 99%
“…The osmolality at which ProP activity is half-maximal (⌸ 1/2 /RT) depends on the structure of the transporter (21,27,28,34,48) and the solvent to which it is exposed (42). The positive correlations among growth medium osmolality, the CL content of E. coli, and ⌸ 1/2 /RT for ProP suggested that ⌸ 1/2 /RT is also elevated by a CL-rich membrane environment (7).…”
Section: Subcellular Locations Of CL Lacymentioning
confidence: 99%
“…When native cysteines are present, however, a cysteine-less version of the protein can be constructed by converting each cysteine to alanine or serine. Previous studies have indicated that such engineered cysteine-less proteins typically retain native structure and function (10,25,37,40). Native cysteines that are protected from labeling by a highly buried location, by involvement in a disulfide bond, or by covalent modification such as myristoylation do not interfere with site-directed spin labeling and can be retained.…”
Section: Site-directed Spin Labelingmentioning
confidence: 99%